Results of study on changes in the body of livestock castrated by unopened method (Mongolian Journal of Agricultural Sciences, 2014)
"Tartu-SHAB" emasculator for unopened castration of male calf, lamb and kids is used to break ductus deferens and blood vessels and damage cremaster muscle after detecting outside the spermatic cord via palpation of scrotal neck skin. Movement of castrated animal becomes slower, hind legs are slightly spread, animal steps on frontal wall of its hind leg hooves and lifts one of hind legs in turn, and superficial, small, painful, differently sized, and warmer swelling appears. Cremaster fascia of testicle tissue castrated animals (at day 30) divides testicle parenchyma into lobules and there are epithelial cells producing spermatozoa at various stages of development in the wall of seminiferous tubules, Sertoli cells and Leydig cells in reticular and soft connective tissues between seminiferous tubules. But at day 60, thickened outer layer of testicle, larger gaps between tubules, structural change of primary and secondary spermatozoa, ceased cellular division cellular division and absence of Leydig cells reveal the process of atrophy. DOI: http://dx.doi.org/10.5564/mjas.v11i2.215 Mongolian Journal of Agricultural Sciences Vol.11(2) 2013 pp.43-48